2015
DOI: 10.1111/joes.12137
|View full text |Cite
|
Sign up to set email alerts
|

Taxation and the User Cost of Capital

Abstract: Abstract. This paper provides a review of the concept of user cost and its determinants. Particular attention is given to the influence of taxation. The concept of user cost relates to the rental, the rate of return to capital, that arises in a profit maximizing situation in which further investment in capital produces no additional profit. This paper sets out in some detail the range of assumptions involved in obtaining alternative expressions for the user cost. The user cost refers to a before-tax capital re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
6
0
3
Order By: Relevance
“…The user cost is the pretax net marginal product of capital and is related to an equilibrium implicit rental price of capital, that is, the opportunity cost of capital (Creedy & Gemmell, 2017). The above expression shows that corporate taxation is associated with a higher user cost of capital, which also includes the marginal adjustment cost corresponding to the replacement investment rate.…”
Section: Because Of the Linear Homogeneity Assumptions We Can Writementioning
confidence: 99%
“…The user cost is the pretax net marginal product of capital and is related to an equilibrium implicit rental price of capital, that is, the opportunity cost of capital (Creedy & Gemmell, 2017). The above expression shows that corporate taxation is associated with a higher user cost of capital, which also includes the marginal adjustment cost corresponding to the replacement investment rate.…”
Section: Because Of the Linear Homogeneity Assumptions We Can Writementioning
confidence: 99%
“…Economic theory indicates that these two provisions had opposite effects on investment since they had opposite effects on how fast businesses can depreciate their capital. When businesses are allowed to depreciate their capital more quickly, their user cost of capital decreases (Hall and Jorgenson, 1967;Creedy and Gemmell, 2015). As the user cost decreases, profit-maximizing businesses increase their investment level and capital stock, driving the marginal product of capital down to the point where the equality between marginal product and user cost is restored.…”
Section: Bonus Depreciation and Amortizationmentioning
confidence: 99%
“…The situation in Europe is searched by Amaral et al (2010), Voth (2003Voth ( , 2002. Current research in this field is focused on the most accurate estimation of costs of capital (Levi and Welch (2017)), influence of taxation (Creedy & Gemmell, 2017), the effect of information (Johnstone, 2016;Plumlee, 2016;Viviani, 2008) and firm growth (Dutta & Nezlobin, 2017) Ekonomicko-manazerske spektrum 2017, Volume XI,Issue 2, and the link between corporate social performance and costs of capital (Suto & Tekehara, 2017). Lambert et al (2007 and suggested a connection between the quality of information and the cost of capital; the impact of a change to the trading system on the costs of capital is described by Chelley-Steeley and Lambertides (2014).…”
Section: Modelling Of Costs Of Capital In Slovak Enterprisesmentioning
confidence: 99%